Metal foil laminate for current collector layer

By using a resin composition of a styrene-based thermoplastic elastomer and a cycloolefin polymer in a metal foil laminate, combined with a conductive filler, the lightweight and flexibility problems of the metal foil laminate in the prior art are solved, and electrolyte resistance and appropriate collector layer performance are achieved.

CN120709379APending Publication Date: 2025-09-26AJINOMOTO CO INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510360541.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-26
Filing Date
2025-03-25
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Conventional technologies have made it difficult to achieve lightweighting of metal foil laminates while maintaining appropriate flexibility and electrolyte resistance, and thinning easily leads to wrinkles and pinholes, making them difficult to apply to production processes.

Method used

A styrene-based thermoplastic elastomer is used as the resin layer of the resin composition, and metal foil layers are formed on both sides thereof. A cycloolefin polymer and a conductive filler are combined, and the thicknesses of the resin layer and the metal foil layer are adjusted to achieve flexibility and electrolyte resistance. The component ratio of the resin composition is optimized by adjusting the repeating unit content and weight-average molecular weight of the styrene-based thermoplastic elastomer.

Benefits of technology

The lightweight metal foil laminate has achieved flexibility and electrolyte resistance, and the conductivity of the collector layer can be freely designed, avoiding the wrinkles and pinhole problems caused by thin filmization, making it suitable for collector layer applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005328509440000151
    Figure BDA0005328509440000151
Patent Text Reader

Abstract

The present invention addresses the problem of providing a metal foil laminate which can maintain appropriate flexibility and electrolyte resistance and which can be reduced in weight. [Solution] A laminate having a resin layer formed from a resin composition containing (A) a styrene-based thermoplastic elastomer, and metal foil layers formed on both surfaces of the resin layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a metal foil laminate for use as a current collecting layer. Background Art

[0002] In 5G and Beyond 5G, as the number of devices assembled in the device increases, there is a tendency for the weight and size of the batteries driving them to become heavier and larger. Therefore, it is expected to reduce the weight while ensuring a certain current. For example, for HAPS and electric vehicles EV that fly in the stratosphere and provide wireless communication services on the ground with solar cell panels and batteries, weight reduction is required, so it is necessary to lightweight the electrodes used in the battery. The demand is met by reducing the thickness of the metal foil used as the collector layer, but there is a technical limit to the thin filmization of metal foil. Ultra-thin metal foil is prone to wrinkles and pinholes, making it difficult to apply to the production process.

[0003] For example, Patent Document 1 discloses a metal foil laminate for a current collecting layer having a resin layer formed from a cured product of a resin composition containing a thermosetting resin, a thermoplastic resin, and a curing agent, and metal foil layers formed on both surfaces of the resin layer.

[0004] However, practical lithium-ion secondary batteries often use lithium hexafluorophosphate, ethylene carbonate, dimethyl carbonate, and other solvents as their electrolytes. Ethylene carbonate, in particular, is a highly polar organic solvent with a high solubility for resins, so resins that can withstand this electrolyte must be selected.

[0005] In addition to carbonaceous materials such as graphite, which have been commonly used as negative electrode materials, negative electrode materials containing elements such as silicon and tin in the active material to increase the negative electrode capacity have also attracted attention. These negative electrode materials tend to expand significantly with charging and discharging. Furthermore, abnormal heating in lithium-ion batteries is mostly caused by short circuits, but in this case, the battery tends to expand due to the generation of internal gas, etc. Therefore, in terms of device safety, it is preferable to have flexibility that can withstand deformation of the contents.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application No. 2023-027749 Summary of the Invention

[0009] Problems to be solved by the invention

[0010] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a metal foil laminate that can achieve weight reduction while maintaining appropriate flexibility and electrolyte resistance.

[0011] Solutions for solving problems

[0012] As a result of intensive research conducted by the present inventors to solve the above-mentioned problems, they discovered that, in a laminate having a resin layer formed from a resin composition and metal foil layers formed on both surfaces of the resin layer, by adopting a styrene-based thermoplastic elastomer as a resin constituting the resin composition, a metal foil laminate can be obtained that can maintain appropriate softness and electrolyte resistance and achieve lightweightness, thereby completing the present invention.

[0013] That is, the present invention has the following features.

[0014] [1] A laminate comprising a resin layer formed from a resin composition containing (A) a styrene-based thermoplastic elastomer, and metal foil layers formed on both surfaces of the resin layer.

[0015] [2] The laminate according to [1], wherein the content of the repeating units having a reactive group in the repeating units constituting the (A) styrene-based thermoplastic elastomer is 0 to 3% by mass relative to the total mass of the (A) styrene-based thermoplastic elastomer.

[0016] [3] The laminate according to [1] or [2], wherein the weight average molecular weight of the (A) styrene-based thermoplastic elastomer exceeds 50,000.

[0017] [4] The laminate according to any one of [1] to [3], wherein the content of the (A) styrene-based thermoplastic elastomer in the resin composition is 50 to 100% by mass relative to 100% by mass of the non-volatile components of the resin composition.

[0018] [5] The laminate according to any one of [1] to [4], wherein the resin composition further contains (B) a cycloolefin polymer.

[0019] [6] The laminate according to [5], wherein the content of the (B) cycloolefin polymer in the resin composition is 5 to 20% by mass relative to 100% by mass of the non-volatile components of the resin composition.

[0020] [7] The laminate according to any one of [1] to [6], wherein the resin composition further contains (C) a conductive filler.

[0021] [8] The laminate according to [7], wherein the content of the (C) conductive filler in the resin composition is 0.5 to 10% by mass relative to 100% by mass of the non-volatile components of the resin composition.

[0022] [9] The laminate according to any one of [1] to [8], wherein the metal foil layer is a copper foil layer.

[0023]

[10] The laminate according to any one of [1] to [9], wherein the thickness of the resin layer is 3 to 60 μm.

[0024]

[11] The laminate according to any one of [1] to

[10] , wherein the elongation at break is 3% or more.

[0025]

[12] The laminate according to any one of [1] to

[11] , wherein the strength ratio is 0.005 or more and 0.95 or less.

[0026] Effects of the Invention

[0027] According to the present invention, compared with the case where the current collecting layer is made of metal foil alone, a metal foil laminate can be provided that is lightweight and has appropriate flexibility and electrolyte resistance. In addition, according to the present invention, the current collecting layer can be freely designed by adjusting the thickness of the metal foil layer and the resin layer, imparting conductivity to the resin layer, etc. DETAILED DESCRIPTION

[0028] Hereinafter, the present invention will be described according to preferred embodiments thereof.

[0029] [Laminated body]

[0030] The laminate of the present invention comprises a resin layer formed from a resin composition containing (A) a styrene-based thermoplastic elastomer, and metal foil layers formed on both surfaces of the resin layer.

[0031] <(A) Styrene-based thermoplastic elastomer>

[0032] In resin combination of the present invention, styrene-based thermoplastic elastomer can only use one, also can and use more than 2 kinds.By using styrene-based thermoplastic elastomer, can obtain keeping suitable flexibility and electrolyte resistance laminate, can be used as the excellent current collecting layer of flexibility and electrolyte resistance and use.

[0033] The styrene-based thermoplastic elastomer is not particularly limited as long as it can exhibit the effects of the present invention, and examples thereof include polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymer (SEBS), polystyrene-polyisobutylene-polystyrene block copolymer (SIBS), polystyrene-polyisobutylene block copolymer (SIB), polystyrene-poly(ethylene-propylene) block copolymer (SEP), polystyrene-poly(ethylene-propylene)-polystyrene triblock copolymer (SEPS), and polystyrene-poly(ethylene / ethylene-propylene)-polystyrene triblock copolymer (SEEPS).

[0034] Examples of commercially available styrene-based thermoplastic elastomers include the "TUFTEC M series" (maleic acid-modified SEBS) manufactured by Asahi Kasei Corporation, the "TUFTECH series" (SEBS) manufactured by Asahi Kasei Corporation, the "SIBSTAR series" (SIBS, SIB) manufactured by Kaneka Corporation, and the "SEPTON series" (SEP, SEPS, SEEP, SEBS) manufactured by Kuraray Co., Ltd.

[0035] From the viewpoint of electrolyte resistance, the content of the repeating unit having a reactive group in the repeating units constituting the styrene-based thermoplastic elastomer is preferably 0 to 20% by mass, more preferably 0 to 15% by mass, further preferably 0 to 10% by mass, and most preferably 0% by mass, relative to the total mass of the styrene-based thermoplastic elastomer.

[0036] From the viewpoint of heat resistance and electrolyte resistance, the weight average molecular weight of the styrene-based thermoplastic elastomer exceeds 50,000 and is 500,000 or less, more preferably 70,000 or more and 400,000 or less, and further preferably 100,000 or more and 300,000 or less. It should be noted that the weight average molecular weight is measured by gel permeation chromatography (GPC) method (converted into polystyrene). Specifically, the weight average molecular weight based on the GPC method can be calculated as follows: using LC-9A / RID-6A manufactured by Shimadzu Corporation as a measuring device, using Shodex K-800P / K-804L / K-804L manufactured by Showa Denko as a column, using chloroform or the like as a mobile phase, measuring at a column temperature of 40°C, and calculating using a standard curve of standard polystyrene.

[0037] From the viewpoint of heat resistance and electrolyte resistance, the content of the styrene unit in the repeating units constituting the styrene-based thermoplastic elastomer is preferably 10 to 50% by mass, more preferably 11 to 45% by mass, and still more preferably 12 to 40% by mass relative to the total mass of the styrene-based thermoplastic elastomer. In addition, repeating units other than the styrene unit are preferably hydrogenated when having an unsaturated bond.

[0038] From the viewpoint of the strength of the resin layer, the content of the styrene-based thermoplastic elastomer in the resin composition of the present invention is preferably 50 to 100 mass %, more preferably 60 to 100 mass %, and even more preferably 65 to 100 mass % relative to 100 mass % of the nonvolatile components of the resin composition.

[0039] <(B) Cycloolefin Polymer>

[0040] Resin combination of the present invention, as long as in the scope of performance effect of the present invention, just can further include cycloolefin polymer (sometimes referred to as " COP " in this manual).Cycloolefin polymer is the polymer that one or both sides in main chain and side chain have the constituent unit that is derived from cyclic olefin.Cycloolefin polymer can be homopolymer, also can be copolymer.Cycloolefin polymer can only use 1 kind, also can use 2 or more kinds.By using cycloolefin polymer, can obtain the laminated body that keeps suitable intensity and electrolyte resistance, can be used as the excellent current collecting layer of intensity and electrolyte resistance and use.

[0041] The cyclic olefin is not particularly limited as long as it can exhibit the effects of the present invention, and may be a polycyclic cyclic olefin or a monocyclic cyclic olefin.

[0042] The polycyclic cyclic olefin is not particularly limited as long as it exhibits the effects of the present invention, and examples thereof include norbornene compounds such as norbornene, methylnorbornene, dimethylnorbornene, ethylnorbornene, ethylidenenorbornene, and butylnorbornene; dicyclopentadiene compounds such as dicyclopentadiene, dihydrodicyclopentadiene, methyldicyclopentadiene, and dimethyldicyclopentadiene; tetracyclododecene, methyltetracyclododecene, dimethyltetracyclododecene; tricyclopentadiene; and tetracyclopentadiene.

[0043] The monocyclic cyclic olefin is not particularly limited as long as it can exhibit the effects of the present invention, and examples thereof include cyclobutene, cyclopentene, cyclooctene, cyclooctadiene, cyclooctatriene, and cyclododecatriene.

[0044] From the viewpoint of forming the resin composition into a film (forming a resin layer), the weight average molecular weight of the cycloolefin polymer is preferably 5000 to 1000000, more preferably 8000 to 200000. It should be noted that the weight average molecular weight is measured using gel permeation chromatography (GPC) (converted to polystyrene). Specifically, the weight average molecular weight based on the GPC method can be calculated as follows: using LC-9A / RID-6A manufactured by Shimadzu Corporation as a measuring device, using Shodex K-800P / K-804L / K-804L manufactured by Showa Denko as a column, using chloroform etc. as a mobile phase, measuring at a column temperature of 40°C, and calculating using a standard curve of standard polystyrene.

[0045] Examples of commercially available cycloolefin polymers include "ZEONOR" manufactured by ZEON Corporation of Japan and "ARTON" manufactured by JSR Corporation.

[0046] The cycloolefin polymer used in the resin composition of the present invention is preferably a cycloolefin copolymer (sometimes referred to as "COC" in this specification) from the viewpoint of flexibility. Cyclic olefin copolymer refers to a polymer having constituent units derived from the above-mentioned cyclic olefin and constituent units derived from non-cyclic olefins such as ethylene and α-olefins. The cycloolefin copolymer may be any of a random copolymer, an alternating copolymer, a block copolymer, and a graft copolymer. As the cycloolefin copolymer, a polymer having constituent units derived from a norbornene compound and constituent units derived from ethylene is preferred. Only one cycloolefin copolymer may be used, or two or more cycloolefin copolymers may be used in combination.

[0047] The α-olefins are not particularly limited as long as they exhibit the effects of the present invention. Examples thereof include linear α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene; and branched α-olefins having 4 to 20 carbon atoms, such as 4-methyl-1-pentene, 3-methyl-1-pentene, and 3-methyl-1-butene.

[0048] The proportion of polymerized units derived from cyclic olefins, particularly polycyclic cyclic olefins, is preferably 3 to 75 mol% based on the total structure of the cyclic olefin copolymer. The proportion of polymerized units derived from acyclic olefins is preferably 5 to 80 mol% based on the total structure of the cyclic olefin copolymer.

[0049] Examples of commercially available cycloolefin copolymers include "TOPAS" manufactured by Polyplastics (a cycloolefin copolymer obtained by copolymerizing norbornene and ethylene) and "APEL" manufactured by Mitsui Chemicals (a cycloolefin copolymer obtained by copolymerizing norbornene and ethylene).

[0050] From the viewpoint of the strength of the resin layer, the content of the cycloolefin polymer in the resin composition of the present invention is preferably 5 to 20% by mass, more preferably 5 to 10% by mass, relative to 100% by mass of the nonvolatile components of the resin composition.

[0051] <(C) Conductive filler>

[0052] In the resin combination of the present invention, in order to improve the electrical conductivity of laminate, it is possible to further contain a conductive filler. As a conductive filler, for example, carbon black, graphite, carbon nanotubes, metal powders (nickel, aluminum, stainless steel (SUS), silver, copper, zinc and titanium etc.), metal oxide powders (tin oxide, indium oxide and zinc oxide etc.), metal coating powders (inorganic materials and organic materials coated with conductive materials etc.) etc. can be enumerated, from the viewpoint of lightweight, preferably carbon black. As carbon black, preferably acetylene black, oil furnace carbon black, gas furnace carbon black, lamp black, channel carbon black etc. Specific examples of carbon black include Raven 760 ULTRA, Raven 780 ULTRA, Raven 790 ULTRA, Raven 1060 ULTRA, Raven 1080 ULTRA, Raven 11 70, Raven 11 90 ULTRA II, Raven 1200, Raven 1250, Raven 1255, Raven 1500, Raven 2000, Raven 2500 ULTRA, Raven 3500, Raven 5000 ULTRA II, Raven 5250, Raven 5750, and Raven 7000 (manufactured by Columbia Carbon Co., Ltd.); Monarch 700, Monarch 800, Monarch 880, Monarch 900, Monarch 1000, Monarch 1100, Monarch 1300, Monarch 1400, Regal 1330R, Regal 1400R, Regal 1660R, and Mogul 1660R. L (all manufactured by Cabot Corporation); Color Black FW1, Color Black FW2, Color Black FW2V, Color Black FW200, Color Black S150, Color Black S160, Color Black S170, Printex 35, Printex U, Printex V, Printex 140U, Printex 140V, Special Black 4, Special Black 4A, Special Black 5, Special Black 6 (all manufactured by Degussa Corporation); MA7, MA8, MA100, MA600, MCF-88, No.25, No.33, No.40, No.47, No.52, No.900, No.2300 (all manufactured by Mitsubishi Chemical Corporation); etc. Examples of carbon nanotubes include single-walled carbon nanotubes (SWCNTs) and double-walled carbon nanotubes (DWCNTs), as well as multi-walled carbon nanotubes (MWCNTs).The conductive filler may be used alone or in combination of two or more.

[0053] For the particle size of the conductive filler, from the viewpoint of forming the resin composition into a film (forming a resin layer), the particle size of the primary particles is preferably 5 μm or less, more preferably 3 μm or less. For example, a filler having a particle size of 0.001 to 3 μm can be used as the primary particle, and a filler having a particle size of 0.005 to 2 μm as the primary particle can be more preferably used. It should be noted that in the present invention, "particle size" can be measured using a laser diffraction particle size distribution meter (JIS Z 8825) or a dynamic light scattering method (JIS Z 8828) or an image analysis method (JIS Z 8827).

[0054] From the perspectives of conductivity and dispersibility, the content of the conductive filler in the resin composition of the present invention is preferably 0.5 to 35% by mass, more preferably 1 to 25% by mass, and even more preferably 3 to 20% by mass, relative to 100% by mass of the non-volatile components of the resin composition. In other embodiments of the present invention, the content of the conductive filler in the resin composition is preferably 0.5 to 10% by mass, relative to 100% by mass of the non-volatile components of the resin composition.

[0055] <Other additives>

[0056] The resin composition of the present invention may further contain additives other than the above-mentioned components, as long as they can achieve the effects of the present invention. Examples of such additives include silane coupling agents; organic fillers such as rubber particles, silicone powder, nylon powder, and fluororesin powder; thickeners such as Orben and Benton; silicone-based, fluorine-based, or polymer-based defoamers or leveling agents; adhesion-imparting agents such as triazole compounds, thiazole compounds, triazine compounds, and porphyrin compounds; and flame retardants such as phosphorus compounds and metal hydroxides.

[0057] <Method for producing resin composition>

[0058] The method for producing the resin composition of the present invention is not particularly limited, and examples thereof include a method in which a solvent or the like is added as needed and the above-mentioned components are mixed using a kneading roll, a rotary mixer, or the like.

[0059] <Resin Layer>

[0060] In the laminate of the present invention, the resin layer is formed from the resin composition described above. The resin layer can be formed on the support by, for example, applying a varnish-like resin composition mixed with an organic solvent to one surface of the support and drying the resulting coating by heating or blowing hot air.

[0061] Examples of the organic solvent include ketones such as acetone, methyl ethyl ketone (sometimes referred to as "MEK" in this specification), and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosolve acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; carbitols such as cellosolve and butyl carbitol; aliphatic hydrocarbons such as methylcyclohexane; aromatic hydrocarbons such as toluene and xylene; dimethylformamide, dimethylacetamide, and N-methylpyrrolidone. Any one of the organic solvents may be used alone, or two or more may be used in combination.

[0062] As the support, there can be mentioned plastic films such as polyethylene, polypropylene, polyvinyl chloride and other polyolefins, cycloolefin polymers, polyethylene terephthalate (sometimes referred to as "PET" in this specification), polyethylene naphthalate and other polyesters, polycarbonate, polyimide and the like. As the plastic film, PET is particularly preferred. In addition, the support may also be a metal foil such as aluminum foil, stainless steel foil, copper foil, etc. For the support, a release treatment, matte treatment, corona treatment, etc. using a silicone resin-based release agent, an alkyd resin-based release agent, a fluororesin-based release agent, etc. may also be implemented on the surface where the resin layer is formed. In the present invention, when the support has a release layer, the release layer is also regarded as a part of the support. The thickness of the support is not particularly limited, but from the viewpoint of operability, etc., it is preferably 20 to 200 μm, more preferably 20 to 125 μm.

[0063] The drying conditions are not particularly limited, but drying at about 50 to 100° C. for about 3 to 15 minutes is usually appropriate.

[0064] From the perspective of lightweighting and electrical resistance, the thickness of the resin layer is preferably 60 μm or less, more preferably 50 μm or less, even more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. From the perspective of layer formation, the lower limit of the thickness of the resin layer is preferably 3 μm or more, more preferably 5 μm or more. In one embodiment of the present invention, the thickness of the resin layer is preferably 3 to 60 μm, more preferably 5 to 50 μm.

[0065] <Metal Foil Layer>

[0066] In the laminate of the present invention, a metal foil layer is formed on both sides of the resin layer. Examples of metals include copper, nickel, aluminum, stainless steel (SUS), silver, and titanium. From the perspective of durability to the electrolyte, copper and nickel are preferred. The method for forming the metal foil layer is not particularly limited, and known techniques, such as wet film-forming methods such as electroless copper plating and electrolytic copper plating, dry film-forming methods such as sputtering and chemical vapor deposition, and combinations thereof, can be used. In addition, when a metal foil layer is formed on a resin layer by vapor deposition, etc., in the event of damage caused by heat during the process, the shrinkage and wrinkling of the resin layer can be suppressed by laminating a slightly adhesive PET film having removable properties (for example, a laminate having a laminate structure of a resin layer / slightly adhesive PET film, a resin layer / support / slightly adhesive PET film, etc., is produced, and a metal foil layer is formed on the resin layer). From the viewpoint of weight reduction and electrical resistance, the thickness of the metal foil layer is preferably 0.005 to 2 μm, more preferably 0.01 to 1.5 μm, and even more preferably 0.02 to 1 μm.

[0067] From the perspective of the strength of the resin layer, the laminate of the present invention preferably has an elongation at break of 3% or more and 15% or less, more preferably 3.5% or more and 12% or less, and even more preferably 4% or more and 10% or less. By setting the elongation at break within this range, a laminate having appropriate flexibility can be obtained. The elongation at break of the present invention is measured at 23°C in accordance with JIS K7127.

[0068] For the laminate of the present invention, from the perspective of the strength and flexibility of the resin layer, its strength ratio is preferably 0.005 or more and 0.5 or less, and more preferably 0.01 or more and 0.4 or less. It should be noted that the strength ratio of the present invention is a value calculated according to the following formula, and the tensile strength can be measured by the method described in the following examples.

[0069] Strength ratio = tensile strength of resin layer / tensile strength of copper foil layer

[0070] If the strength ratio is less than 0.005, the tensile strength of the copper foil layer becomes too high relative to the tensile strength of the resin layer. On the other hand, if the strength ratio exceeds 0.5, the tensile strength of the resin layer becomes too high relative to the tensile strength of the copper foil layer.

[0071] [Method for producing laminate]

[0072] The method for manufacturing the laminate of the present invention is not particularly limited, and for example, the following method can be cited: a resin layer is formed on a support as described in the above-mentioned item "Resin layer", a protective film is laminated on the surface of the resin layer on the opposite side of the support as needed to obtain a sheet, and then a metal foil layer is formed on the resin layer (exposed by peeling off the protective film as needed) as described in the above-mentioned item "Metal foil layer", and then a metal foil layer is similarly formed on the resin layer exposed by peeling off the support.

[0073] As the protective film, there can be mentioned plastic films such as polyethylene, polypropylene, polyvinyl chloride and other polyolefins, cycloolefin polymers, PET, polyethylene naphthalate and other polyesters, polycarbonate, polyimide and the like. As the plastic film, PET is particularly preferred. In addition, the protective film may also be a metal foil such as aluminum foil, stainless steel foil, copper foil and the like. For the protective film, a release treatment using a silicone resin-based release agent, an alkyd resin-based release agent, a fluororesin-based release agent and the like, a matte treatment, a corona treatment and the like may also be applied on the surface in contact with the resin layer. In the present invention, when the protective film has a release layer, the release layer is also regarded as a part of the protective film. The thickness of the protective film is not particularly limited, but is preferably 20 to 200 μm, more preferably 20 to 125 μm, from the viewpoint of operability and the like.

[0074] [use]

[0075] The laminate of the present invention can be suitably used, for example, as a current collecting layer, particularly as a current collecting layer of a negative electrode of a battery.

[0076] Example

[0077] The present invention will be described in more detail below with reference to Examples. However, the present invention is not limited to the following Examples and can be implemented with appropriate modifications within the scope of the above and below-described gist. Such modifications are encompassed within the technical scope of the present invention. It should be noted that, unless otherwise specified, "parts" and "%" in the amounts of components and copolymerization units refer to "parts by mass" and "% by mass," respectively.

[0078] <ingredients>

[0079] The components used in Examples and Comparative Examples are shown below.

[0080] (A) Styrene-based thermoplastic elastomer:

[0081] Maleic acid-modified SEBS ("TUFTEC M1911" manufactured by Asahi Kasei Corporation, weight-average molecular weight: 82,000)

[0082] SEBS ("TUFTEC H1043" manufactured by Asahi Kasei Corporation, weight average molecular weight: 141,000)

[0083] SIBS ("SIBSTAR 103T-UL" manufactured by Kaneka Corporation, weight average molecular weight: 70,000)

[0084] SEPS ("SEPTON 2004F" manufactured by Kuraray Co., Ltd., weight average molecular weight: 60,000)

[0085] (B) Cyclic olefin polymer:

[0086] Cyclic olefin copolymer ("TOPAS 5013L" manufactured by Polyplastics; COC obtained by copolymerization of norbornene and ethylene)

[0087] Cyclic olefin copolymer ("APEL 6011T" manufactured by Mitsui Chemicals; COC obtained by copolymerization of norbornene and ethylene)

[0088] (C) Conductive filler:

[0089] Carbon black (average particle size 50 nm (measured by image analysis (JIS Z 8827)), "#20" manufactured by Mitsubishi Chemical Corporation)

[0090] Carbon nanotubes (OCSiAl "TUBALL615", carbon nanotube content 10%)

[0091] Others (Comparative Example ingredients):

[0092] A mixture of liquid bisphenol A epoxy resin and liquid bisphenol F epoxy resin ("ZX-1059" manufactured by Nippon Steel Chemicals & Materials Co., Ltd., epoxy equivalent: approximately 165 g / eq)

[0093] Phenoxy resin solution ("YX7200B35" manufactured by Mitsubishi Chemical Corporation, solvent: MEK, non-volatile content: 35%, epoxy equivalent: approximately 8000 g / eq)

[0094] "2E4MZ" (curing agent) manufactured by Shikoku Chemical Industry Co., Ltd.

[0095] San-Apro's "U-CAT3512T" (curing accelerator)

[0096] Salicylic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.; curing accelerator)

[0097] <Example 1>

[0098] Varnishes with the blending ratios shown in the table below were prepared according to the following procedures, and laminates were prepared using the resulting varnishes. The amounts (parts) of the components listed in the table below represent the amount of non-volatile components in the varnish. Specifically, 50 parts of an acid-modified polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymer (SEBS) ("M1911" manufactured by Asahi Kasei Corporation) were added. Toluene solvent was added to prepare a 30% non-volatile solution for uniform coating, and the mixture was uniformly dispersed using a high-speed rotary mixer to obtain a varnish.

[0099] The obtained varnish was evenly applied onto the release-treated surface of a support (polyethylene terephthalate film treated with a silicone-based release agent, 38 μm thick, hereinafter referred to as “release PET film”) using a die coater in such a manner that the thickness of the resin layer after drying became 10 μm. After drying at 120°C for 10 minutes, a release PET film as a protective film was attached to the surface of the formed resin layer in such a manner that the release-treated surface thereof was in contact with the resin layer, thereby obtaining a sheet having a laminated structure of support / resin layer / protective film.

[0100] The protective film of the obtained sheet is peeled off, and a copper foil layer (thickness: 0.2 μm) is formed on the exposed resin layer by vapor deposition. Then, the support is peeled off, and a copper foil layer (thickness: 0.2 μm) is similarly formed on the exposed resin layer to produce a laminate having a laminate structure of copper foil layer / resin layer / copper foil layer.

[0101] <Example 2>

[0102] A laminate having a laminate structure of copper foil layer / resin layer / copper foil layer was prepared using the same method as in Example 1, except that 25 parts of polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymer (SEBS) ("H1043" manufactured by Asahi Kasei Corporation) and 25 parts of polystyrene-polyisobutylene-polystyrene block copolymer (SIBS) ("103T-UL" manufactured by Kaneka Corporation) were used instead of acid-modified polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymer (SEBS) ("M1911" manufactured by Asahi Kasei Corporation).

[0103] <Example 3>

[0104] A laminate having a laminate structure of copper foil layer / resin layer / copper foil layer was prepared using the same method as in Example 1, except that 50 parts of a polystyrene-poly(ethylene-propylene)-polystyrene triblock copolymer (SEPS) (“2004F” manufactured by Kuraray Co., Ltd.) was used instead of a modified polystyrene-poly(ethylene-butylene)-polystyrene triblock copolymer (SEBS) (“M1911” manufactured by Asahi Kasei Corporation) and 5 parts of a cycloolefin copolymer (“5014CL” manufactured by Mitsui Chemicals, Inc.) was further blended.

[0105] <Example 4>

[0106] A laminate having a laminate structure of copper foil layer / resin layer / copper foil layer was produced by the same method as in Example 1 except that 10 parts of a cycloolefin copolymer ("6011T" manufactured by Mitsui Chemicals, Inc.) was further blended.

[0107] <Example 5>

[0108] A laminate having a laminate structure of copper foil layer / resin layer / copper foil layer was produced by the same method as in Example 1 except that 2.5 parts of a cycloolefin copolymer ("6011T" manufactured by Mitsui Chemicals, Inc.) was further blended.

[0109] <Example 6>

[0110] A laminate having a laminate structure of copper foil layer / resin layer / copper foil layer was produced by the same method as in Example 1 except that 2.5 parts of carbon black (average particle size 50 nm, "#20" manufactured by Mitsubishi Chemical Corporation) was further compounded.

[0111] <Example 7>

[0112] A laminate having a laminate structure of copper foil layer / resin layer / copper foil layer was produced by the same method as in Example 1 except that 50 parts of carbon black (average particle size 50 nm, "#20" manufactured by Mitsubishi Chemical Corporation) was further blended.

[0113] <Example 8>

[0114] A laminate having a laminate structure of copper foil layer / resin layer / copper foil layer was prepared in the same manner as in Example 1 except that 5 parts of carbon nanotubes ("TUBALL 615" manufactured by OCSiAl Corporation, carbon nanotube content 10%) were further blended.

[0115] <Comparative Example 1>

[0116] A commercially available copper foil (thickness 5 μm) was used instead of the laminate having a laminate structure of copper foil layer / resin layer / copper foil layer.

[0117] <Comparative Example 2>

[0118] A commercially available PET film (thickness 5 μm) was used instead of the laminate having a laminate structure of copper foil layer / resin layer / copper foil layer.

[0119] <Comparative Example 3>

[0120] A mixture of 80 parts of a liquid bisphenol A epoxy resin and a liquid bisphenol F epoxy resin ("ZX-1059" manufactured by Nippon Steel Chemicals & Materials Co., Ltd.) and 120 parts of a phenoxy resin solution ("1256B40" manufactured by Mitsubishi Chemical Corporation) was mixed and uniformly dispersed using a high-speed rotary mixer to obtain a mixture. Furthermore, 5 parts of a curing accelerator ("U-CAT3512T" manufactured by San-Apro), 0.5 parts of a curing accelerator ("salicylic acid" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 2 parts of a curing agent ("2E4MZ" manufactured by Shikoku Chemicals Co., Ltd.) were mixed and uniformly dispersed using a high-speed rotary mixer to obtain a varnish of a resin composition.

[0121] The obtained varnish was uniformly coated on a support (polyethylene terephthalate film treated with a non-silicone release agent, thickness 38 μm, hereinafter referred to as “release PET film”) using a die coater in such a manner that the thickness of the resin composition layer after drying became 10 μm. After drying at 80°C for 10 minutes, a release PET film as a protective film was attached to the surface of the formed resin composition layer in such a manner that its release-treated surface was in contact with the resin composition layer, thereby obtaining a sheet having a laminated structure of support / resin composition layer / protective film.

[0122] The protective film of the obtained sheet was peeled off, and a copper foil with a carrier (carrier: PET; thickness: 38 μm; copper foil thickness: 0.2 μm) was laminated on the exposed resin composition layer. Then, the support was peeled off, and a copper foil with a carrier (carrier: PET; thickness: 38 μm; copper foil thickness: 0.2 μm) was laminated on the exposed resin composition layer. The mixture was heated and pressed under conditions of 80°C and 0.3 MPa, and heated in an oven at 100°C for 60 minutes to thermally cure the resin composition layer to produce a laminate having a laminate structure of copper foil layer / resin layer / copper foil layer.

[0123] The laminates, copper foils, and PET films obtained in Examples and Comparative Examples were evaluated by the following methods.

[0124] <Evaluation of film properties>

[0125] The states of the laminates obtained in Examples and Comparative Examples were determined as follows.

[0126] ○ (good): The film (resin layer) is well formed and can be used as a current collecting layer

[0127] × (bad): A film (resin layer) can be formed, but the viscosity is strong and cannot be used as a collector layer; or a film (resin layer) can be formed, but the adhesion to the copper foil layer is weak and cannot be used as a collector layer; or a film cannot be formed

[0128] <Weight Evaluation>

[0129] The laminates, copper foils, and PET films obtained in Examples and Comparative Examples were cut into 5 cm squares, and the weights were measured using a precision balance to calculate the weight per unit area.

[0130] ○ (good): Weight per unit area is less than 5 mg / cm 2

[0131] × (bad): weight per unit area is 5 mg / cm 2 above

[0132] <Evaluation of resistance value>

[0133] The laminates, copper foils, and PET films obtained in Examples and Comparative Examples were cut into 5 cm squares, and their surface resistance values ​​were measured using a low-resistivity meter (MCP-T700, manufactured by Mitsubishi Chemical Analytech) using a four-probe method.

[0134] ○(Good): Resistance value is less than 1Ω / mouth

[0135] × (bad): Unable to measure due to resistance value of 1Ω / □ or higher or high resistance

[0136] <Evaluation of Electrolyte Resistance>

[0137] The laminates, copper foil, and PET film obtained in the Examples and Comparative Examples were cut into 5 cm squares, and their initial weights were measured using a precision balance. A container containing dimethyl carbonate was prepared, and the laminate, copper foil, and PET film were immersed in the dimethyl carbonate and allowed to sink for 24 hours. After this period, the laminate, copper foil, and PET film were removed, the yarn ends were overlapped, and the dimethyl carbonate adhering to the laminate, copper foil, and PET film was thoroughly removed. The weight was then measured using a precision balance. The weight change rate was calculated using the following formula, and the determination was made as follows.

[0138] Weight change rate (%) = |(weight after dimethyl carbonate immersion - initial weight) / initial weight| × 100

[0139] ○ (good): Weight change rate is less than 5%

[0140] × (bad): Weight change rate is 5% or more

[0141] <Evaluation of Elongation at Break>

[0142] The laminates, copper foils, and PET films obtained in Examples and Comparative Examples were cut into dumbbell shapes and their elongation at break at 23° C. was measured using a tensile tester “RTC-1250A” manufactured by Orientec in accordance with JIS K7127 and evaluated based on the following criteria.

[0143] ○ (good): Elongation at break is 3% or more and less than 15%

[0144] × (bad): Elongation at break is less than 3% or 15% or more

[0145] The laminate whose elongation at break was evaluated as “◯ (good)” can have appropriate flexibility.

[0146] <Intensity Ratio>

[0147] The resin layer obtained from the sheets having a laminated structure of support / resin layer / protective film produced in the Examples and Comparative Examples was cut into a dumbbell shape and its tensile strength at 23°C was measured using an "RTC-1250A" tensile testing machine manufactured by Orientec in accordance with JIS K7127. The measured tensile strength was used to calculate the strength ratio compared to the copper foil layer using the following formula.

[0148] Strength ratio = tensile strength of resin layer / tensile strength of copper foil layer

[0149]

Table 1

[0150]

[0151] Note) Comparative Example 1: The tensile strength of the copper foil was set to 1.000.

[0152] Comparative Example 2: Tensile Strength of PET Film / Tensile Strength of Copper Foil Layer

[0153] In addition, in Table 1,

[0154] Regarding the resin layer thickness, since Comparative Examples 1 and 2 do not have a resin layer, they are expressed as “-”.

[0155] Regarding the total thickness of the metal foil layer, since Comparative Example 2 does not have a metal foil layer, it is expressed as “-”.

[0156] Regarding the thickness of the PET layer, since Examples 1 to 8 and Comparative Examples 1 and 3 did not have a PET layer, they were expressed as “-”.

[0157] Regarding the evaluation of film formation, Comparative Examples 1 and 2 had no film (resin layer) and were not evaluated for film formation, so they were expressed as "-".

[0158] As can be seen from the results in Table 1, the laminates of Examples of the present invention were good in terms of film properties, weight, electrical resistance, electrolyte resistance, and elongation at break.

[0159] Industrial applicability

[0160] The laminate of the present invention can be lightweight while maintaining appropriate flexibility and electrolyte resistance, and therefore can be suitably used as a current collecting layer, particularly a current collecting layer of a negative electrode of a battery.

Claims

1. A laminate comprising a resin layer formed from a resin composition containing (A) a styrene-based thermoplastic elastomer, and metal foil layers formed on both surfaces of the resin layer.

2. The laminate according to claim 1, wherein The content of the repeating unit having a reactive group in the repeating units constituting the (A) styrene-based thermoplastic elastomer is 0 to 3% by mass based on the total mass of the (A) styrene-based thermoplastic elastomer.

3. The laminate according to claim 1, wherein The weight average molecular weight of the (A) styrene-based thermoplastic elastomer exceeds 50,000.

4. The laminate according to claim 1, wherein The content of the (A) styrene-based thermoplastic elastomer in the resin composition is 50 to 100% by mass relative to 100% by mass of the non-volatile components of the resin composition.

5. The laminate according to claim 1, wherein The resin composition further contains (B) a cycloolefin polymer. The laminate according to claim 5 , wherein: The content of the (B) cycloolefin polymer in the resin composition is 5 to 20% by mass relative to 100% by mass of the non-volatile components of the resin composition.

7. The laminate according to claim 1, wherein The resin composition further contains (C) a conductive filler.

8. The laminate according to claim 7, wherein The content of the (C) conductive filler in the resin composition is 0.5 to 10% by mass relative to 100% by mass of the non-volatile component of the resin composition.

9. The laminate according to claim 1, wherein The metal foil layer is a copper foil layer.

10. The laminate according to claim 1, wherein The thickness of the resin layer is 3 to 60 μm.

11. The laminate according to claim 1, wherein The elongation at break is more than 3%.

12. The laminate according to claim 1, wherein The intensity ratio is 0.005 or more and 0.95 or less.

Citation Information

Patent Citations

  • Method and apparatus for determining broadcasting style, equipment, and computer storage medium

    JP2023027749A